THE ROLE OF E-LEARNING MULTIMEDIA (EDUCATIONAL VIDEO) IN IMPROVING THE KNOWLEDGE OF RADIOLOGY RESIDENTS ABOUT NASOPHARYNGEAL CANCER STAGING (Department of Radiology, Medical Faculty, University of Brawijaya, 2025)
Approximately 13,000 new cases of nasopharyngeal carcinoma (NPC) are reported annually in Indonesia, where it ranks as the fourth most common cancer, with an incidence rate of 6.2 per 100,000 person-years. CT scans and magnetic resonance imaging (MRI) are crucial radiological techniques for more accurate and precise diagnosis of NPC. Staging NPC, as outlined in the 8th edition of the American Joint Committee on Cancer (AJCC), is essential for determining the optimal treatment approach. Educational videos are valuable e-learning tools for disseminating knowledge in the digital era. These videos offer the advantages of being recorded for later viewing and reducing content-related grammatical issues. This study employs a one-group pre- and post-intervention design within a quasi-experimental framework. Purposive sampling was used to select thirty-three participants, and sample data were collected based on their completion of assessments before and after watching the instructional video in June 2024. Statistical analysis of the hypothesis was conducted using SPSS version 25.0. Research findings revealed that educational videos significantly enhanced the understanding of NPC staging among radiology residents. The Wilcoxon Test showed higher post-intervention scores compared to pre-intervention scores, indicating a significant difference (p = 0.003, < 0.05), which demonstrates that watching educational videos positively influenced knowledge improvement.